Analisis Pengaruh Bauran Pemasaran Terhadap Kepuasan dan Loyalitas Pelanggan di Karita Muslim Square Yogyakarta - Richa Angkita Mulyawisdawati (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2012)
Syari’ah marketing is a business discipline strategies that directs to the process of supply, demand and value alteration from an initiator to its stakeholders based on Islamic principles. And also about customer’s satisfaction which is a basic concept of marketing and success factor for organization in business as well. It could be viewed from the fact that there are many companies emphasize the importance of giving their customers high level of satisfaction. Most companies measure the satisfaction of their customer and hope the customer will loyal in choosing the company’s product or service, if the customer satisfaction is high. So that it would cause the customer’s loyalty to the company.This research is attempted to measure the influence of marketing mix which are consist of four aspects product, price, location or distribution and promotion to the customer’s satisfaction, then their accordance to Islamic Principles and to measure the influence of customer’s satisfaction to customer’s loyalty in Karita Muslim Square Yogyakarta. This research is an analytic descriptive research in quantitative and qualitative uses the method of distributing questionnaire in order to gain primary data by non probability sampling technique for 100 respondents of the customer of Karita Muslim Square Yogyakarta. The result of this research shows that product and price significantly influence to the customer’s satisfaction. But location or distribution gives the negative influence and doesn’t significantly toward the customer’s by the standardized coefficient value -0.26, while promotion gives the positive influence but doesn’t significantly toward customer’s satisfaction by the significant value 0.467 á (0.05). Price is the strongest aspect which gives the influence to customer’s satisfac- tion by the significance value 0,000. Meanwhile, from simple regression it was proven that customer satisfaction positively influence loyalty intentions. Those four marketing mix which were offered by Karita Muslim Square have been according to Islamic Principles as have appropriated by Al-Qur’an and Hadits teachings.